2011
DOI: 10.1590/s1415-47572011005000014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and geographical Relationship of Asian barley landraces using SSRs

Abstract: Genetic diversity in 403 morphologically distinct landraces of barley (Hordeum vulgare L. subsp. vulgare) originating from seven geographical zones of Asia was studied using simple sequence repeat (SSR) markers from regions of medium to high recombination in the barley genome. The seven polymorphic SSR markers representing each of the chromosomes chosen for the study revealed a high level of allelic diversity among the landraces. Genetic richness was highest in those from India, followed by Pakistan while it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…This loss is a reflection of the fact that almost 50 % of diversity is distributed among populations for inbred species (LOVELESS and HAMRICK, 1984). For example, NAEEM et al (2011) reported genetic diversity among populations to be 40% compared to 60 % within populations of Asian barley. However, maize provides an example of a domesticated form which maintained a high level of genetic diversity, although it is highly differentiated from its wild ancestor (LEFEVRE, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This loss is a reflection of the fact that almost 50 % of diversity is distributed among populations for inbred species (LOVELESS and HAMRICK, 1984). For example, NAEEM et al (2011) reported genetic diversity among populations to be 40% compared to 60 % within populations of Asian barley. However, maize provides an example of a domesticated form which maintained a high level of genetic diversity, although it is highly differentiated from its wild ancestor (LEFEVRE, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[13,42] reported average PIC values of 0.78 and 0.73 from ICARDA and Ethiopia, respectively. In contrast, lower PIC values of 0.58, 0.54 and 0.46 were reported by [57][58][59], respectively. In general, a PIC value greater than 0.5 is useful in genetic studies since it can distinguish a marker's polymorphism [60].…”
Section: Discussionmentioning
confidence: 69%
“…Allelic diversity is vital for delineating the potential of germplasm for further conservation studies and crop improvement. Previous reports have used SSRs in determining the number of alleles and alleles per locus in various food crops [18,19,10]. In general, as the number of cultivars in any given population increased so did the diversity and the number of alleles/locus.…”
Section: Discussionmentioning
confidence: 99%